(untitled) (Global Journal of Computer Science and Technology, 2014)
Efficient mobility management techniques are critical to the success of next-generation wireless systems. Handoff management, which is one of the two basic functions of mobility management, has become more critical in fourth generation wireless networks which support multimedia services. The paper treats basic issues involved in handoff management aspect of general mobility management in wireless communication systems. The relevance of mobility management, handoff management, and general mobility management protocols are explained. The taxonomy of handoff mechanisms, causes of delays in handoffs, and security in handoff procedures are elicited. The paper concludes highlighting some open areas of research in providing seamless services.